An assessment of the potential for utilisation of soil-stored seed, from on- and off 'conservation islands' (isolated mountains), as an indicator of restoration potential of degraded sites in semi-arid Karoo areas - Jones, F. Elizabeth (Freda Elizabeth) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2000.